The common link and its relation to the Madār - (:unkn) unknown (Brill Academic Publishers, 2004)
I examine here the use of the term madār in the Muslim hadīth literature in an effort to reassess G.H.A. Juynboll's claim that this term is equivalent to his common link. I argue that there are significant differences between the understanding and use of madār by both classical and contemporary Muslim scholars, on the one hand, and Juynboll's notion of the common link, on the other. After summarizing Juynboll's conclusions, I present and discuss some examples of the use of madār chosen from authoritative hadīth commentaries and rijāl books; discuss how Muslim scholars understood the term madār; and reevaluate Juynboll's ideas about the related terms, mutābi'āt and shawāhid. © Koninklijke Brill NV, Leiden, 2004